AN ECONOMIC ORDER QUANTITY MODEL WITH RAMP TYPE DEMAND RATE, CONSTANT DETERIORATION RATE AND UNIT PRODUCTION COST - Manna, Prasenjit; Manna, Swapan Kumar; Giri, Bibhas Chandra (Yugoslav Journal of Operations Research; Vol 26 No 3 (2016), 2016)
We have developed an order level inventory system for deteriorating items with demand rate as a ramp type function of time. The finite production rate is proportional to the demand rate and the deterioration rate is independent of time. The unit production cost is inversely proportional to the demand rate. The model with no shortages case is discussed considering that: (a) the demand rate is stabilized after the production stopping time and (b) the demand is stabilized before the production stopping time. Optimal costs are determined for two different cases.